2021
DOI: 10.5588/ijtld.21.0022
|View full text |Cite
|
Sign up to set email alerts
|

Bedaquiline for multidrug-resistant TB in paediatric patients

Abstract: BACKGROUND: TMC207-C211 (NCT02354014) is a Phase 2, open-label, multicentre, single-arm study to evaluate pharmacokinetics, safety/tolerability, antimycobacterial activity and dose selection of bedaquiline (BDQ) in children (birth to <18 years) with multidrug-resistant-TB (MDR-TB).METHODS: Patients received 24 weeks’ BDQ with an anti-MDR-TB background regimen (BR), followed by 96 weeks of safety follow-up. Results of the primary analysis are presented based on data up to 24 weeks for Cohort 1 (≥12–<18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Obstacles to the implementation of these shorter regimens in children include insufficient evidence around safety and dosing schedules. To this end, there is now accumulating data on the safe use of bedaquiline in children and the WHO now recommends its use in both short and long drug-resistant-TB treatment regimens and provides dosing schedules for children of all ages [60 ▪ ]. Similarly, the use of delamanid has been extended to children less than 3 years of age [61].…”
Section: Tuberculosis Treatment For Childrenmentioning
confidence: 99%
“…Obstacles to the implementation of these shorter regimens in children include insufficient evidence around safety and dosing schedules. To this end, there is now accumulating data on the safe use of bedaquiline in children and the WHO now recommends its use in both short and long drug-resistant-TB treatment regimens and provides dosing schedules for children of all ages [60 ▪ ]. Similarly, the use of delamanid has been extended to children less than 3 years of age [61].…”
Section: Tuberculosis Treatment For Childrenmentioning
confidence: 99%
“…8 In the ongoing pediatric TMC207-C211 phase 2 study, safety data among 30 children in 2 cohorts (15, 5–10 years and 15, 14–17 years of age) receiving WHO-recommended RR-TB regimens including bedaquiline, indicated that 6 (40%) children had QTcF increase of 30–60 ms from baseline but none had QTcF >460 ms over 24 weeks. 9 In an observational pharmacokinetic study of 15 children and adolescents 6–16 years old receiving bedaquiline-containing regimens for RR-TB in routine care, 2 (13%) had mildly prolonged QTcF up to 480 ms but none had QTcF >500 ms. 10 Interim safety data from another ongoing bedaquiline pharmacokinetic study indicate that 3 (27%) of 11 children <6 years of age receiving RR-TB treatment had QTcF increase of 30–60 ms and all received concomitant clofazimine. 3…”
Section: Current Knowledge On Qt Interval Prolongation With Second-li...mentioning
confidence: 99%
“…For instance, moxifloxacin and levofloxacin, two second-line anti-TB fluoroquinolones also induce QT-prolongation [6]. However, bedaquiline still has an excellent safety profile compatible with the development of a paediatric formulation [7,8]. In 2019, pretomanid, which belongs to the same drug class as delamanid, received approval by the US FDA under its Limited Population Pathway for Antibacterial and Antifungal Drugs.…”
Section: Market Overviewmentioning
confidence: 99%